Advanced Wearable Thermocells for Body Heat Harvesting. Issue 48 (1st October 2020) - Liu, Yuqing; Zhang, Shuai; Zhou, Yuetong; Buckingham, Mark A.; Aldous, Leigh; Sherrell, Peter C.; Wallace, Gordon G.; Ryder, Gregory; Faisal, Shaikh; Officer, David L.; Beirne, Stephen; Chen, Jun
Abstract: Thermoelectrochemical cells (thermocells) designed for harvesting human body heat can provide constant power output for wearable electronics, supplementing state‐of‐the‐art flexible power storage and conversion solutions. However, a systematic investigation into the optimization of wearable thermocells is lacking, especially with regard to device design, n‐type electrolytes, and electrode/electrolyte integration. Here, a n‐type gel electrolyte: polyvinyl alcohol‐FeCl2/3 with outstanding flexibility and elasticity and exceptional electrolyte/electrode integration into a 3D porous poly(3, 4‐ethylenedioxythiophene)/polystyrenesulfonate (PEDOT/PSS) electrode, is produced via an in situ chemical crosslinking method. The integrated n‐type cell shows excellent seebeck coefficients (0.85 mV K −1 ) and output current density (1.74 A m −2 K −1 ) that are comparable with an optimized p‐type cell consisting of a carboxymethylcellulose‐K3/4 Fe(CN)6 electrolyte with a 3D PEDOT/PSS‐edge functionalized graphene/carbon nanotube electrode (−1.22 mV K −1 and 1.85 A m −2 K −1 ). The equivalent performance of the n‐type and p‐type cells enables the effective series connection of up to 18 pairs of p–n cells that combines to give an output voltage of 0.34 V (∆T = 10 K). This in‐series device is fabricated into a proof‐of‐concept watch strap, which can harvest body heat, charge supercapacitor (up to 470 mF) as well as illuminate a green light emitting diode, demonstrating the practical applications. Abstract : A proof‐of‐concept of high‐performance wearable thermocell is made through systematic investigations into wearable thermocells with regard to the development of n‐type gel electrolytes, the integration of gel electrolytes into 3D porous electrode, and advanced device design. The demonstration of wearable thermocells harvesting body heat, charging supercapacitors and illuminating LED lights, shows the potential for commercial applications.